Penelitian Praktis Model Blanded Learning Berbasis SPOC pada Matematika Tingkat Lanjut - Wang, Fang; Du, Wen (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Jambi, 2024)
Based on the current situation of advanced mathematics curriculum teaching, this study first constructs a blended learning model for advanced mathematics based on SPOC through literature research from three aspects: curriculum design, teaching implementation, and learning evaluation. And designs a specific blended teaching case combined with the